Pemberlakuan Syari'at Islam Di Nanggroe Aceh Darussalam (NAD) - Muhammad Abdul Kholiq (Fakultas Hukum Universitas Islam Indonesia, 2005)
The application of Islamic Syariah to Nanggroe Aceh Darussalam which has already obtained speciai autonomy, based on its historically background which has a specific nature and it has already become the ideology and political agenda of the society. In addition, there is justification based on the religious doctrine in theory of Islamic Law Reception Authority, and it also is supported by the historicai facts. Even, the application of Islamic Syariah especially to the adherent of religion, it becomes Constitutional Right to the Moslems in Indonesia. It should become the obligation of a State to facilitate and guarantee the realization.